Orderlikey : Smart Kiosk Ordering System For FK - Muhammad Adam Iskandar, Japri (2023)
This thesis presents the development of Orderlikey, a web-based smart kiosk ordering system designed to address the challenges faced by the Faculty of Computing (FK) cafeteria and kiosk at the University of Malaysia Pahang (UMP). The system aims to improve the ordering process by reducing order processing time and human errors, ultimately enhancing customer satisfaction. The research begins with an introduction to the importance of food and beverage (F&B) in the restaurant industry and the role of technology in transforming the F&B sector. The problems faced by the FK kiosk, such as menu updates, manual calculations, and inconsistent scheduling, are identified as the motivation for developing Orderlikey. The objectives of the project include identifying the system's modules and features, developing a web-based application with a mobile friendly interface, and conducting user acceptance testing (UAT) to ensure the system meets the requirements and expectations of its intended users. The project's significance lies in its ability to enhance the ordering process, reduce errors, and improve overall efficiency. The development of Orderlikey is informed by a comparative analysis of existing systems, including self-ordering systems (SOS), point-of-sale (POS) systems, and kitchen display systems (KDS). The features and benefits of these systems are integrated into Orderlikey to overcome the identified disadvantages. The system allows customers to view updated menus, prices, and kiosk information, while kiosk staff can manage orders, menu items, and kiosk details through any modern web browser device. The UAT process involves end-users and stakeholders using Orderlikey in a real-world scenario to identify any issues or discrepancies. This testing phase ensures that the system is ready for deployment and meets user expectations. The thesis concludes with a summary of the objectives achieved, limitations faced during the project, and potential areas for future work, including integration with online ordering platforms, payment gateways, advanced analytics and reporting, loyalty programmes, and multi-language support. Overall, Orderlikey presents an innovative and efficient solution to improve the FK kiosk ordering process, providing convenience, accuracy, and enhanced customer satisfaction.